Antioxidant and anti-inflammatory protective effects of yellowtail (Seriola quinqueradiata) milt hydrolysates on human intestinal epithelial cells in vitro and dextran sodium sulphate-induced mouse colitis in vivo. Issue 18 (7th September 2022) - Li, Shiyang; Yuan, Ning; Guo, Wei; Chai, Yuan; Song, Yi; Zhao, Yuanhui; Zeng, Mingyong; Wu, Haohao
Abstract : Yellowtail milt hydrolysates have considerable antioxidant and anti-inflammatory efficacies to maintain gut health. Abstract : Milt is an underutilized fish processing by-product containing valuable nutrients for human health. Here, a gastrointestinal hydrolysate of degreased yellowtail ( Seriola quinqueradiata ) milt contained 70.6% arginine-rich protein, 20% nucleic acids, 7.1% minerals and 2.3% carbohydrates. Yellowtail milt hydrolysates (YMH) effectively attenuated the H2 O2 -induced burst of intracellular reactive oxygen species, plasma membrane impairment, loss of cell viability, interleukin 8 production and the expression of claudin-4 and occludin in Caco-2 cells with its protein fraction playing a greater antioxidant role than its nucleic acid fraction. YMH also significantly counteracted the tumor necrosis factor α- and interleukin 1β-stimulated interleukin 8 production and cyclooxygenase-2 and inducible nitric oxide synthase expression in Caco-2 cells and inhibited the production of nitric oxide and proinflammatory mediators in lipopolysaccharide-stimulated RAW 264.7 cells depending on its protein fraction, rather than its nucleic acid fraction. YMH and a positive drug 5-aminosalicylic acid were intragastrically administered to C57BL/6 mice daily for 7 days during and after 4-day dextran sodium sulphate exposure. Based on clinical signs, colon histopathology and biochemical analysis of colonic tight junction proteins, mucus compositions and goblet cells, YMH ameliorated mouse colitis symptoms and intestinal epithelial barrier dysfunction more effectively than 5-aminosalicylic acid. According to myeloperoxidase activity, proinflammatory cytokines and NF-κB, YMH and 5-aminosalicylic acid exerted equivalent inhibitory effects on colonic and systemic inflammation. Overall, YMH have considerable antioxidant and anti-inflammatory efficacies to maintain gut health.